An Empirical Study on Awqaf Endowers’ Perception: Imperatives for Awqaf Institutions’ Success - Fuadah Johari; Nursilah Ahmad; Syadiyah Abdul Shukor; Muhammad Ridhwan Ab. Aziz; Zurina Kefeli@ Zulkefli; Mohammad Haji Alias; Kalsom Abd Wahab; Nor Masitah Mohd Orip; Fauzi Abu Hussin; Patmawati Ibrahim (Universiti Sains Islam Malaysia, 2024)
The success of awqaf institutions are determined by many factors, among others is good feedback from the endowers either from their contribution or repeat endowing. This study investigates the perception of endowers to endow and factors motivating them to repeat endowing in ensuring waqf institution success among 366 respondents in 2014. The study employs two models of multiple linear regression analysis. The first model examines the determinant factors influencing the intention to endow whereas the second model investigates internal and external factors influencing the intention to repeated waqf endowment in future. The findings show integrity of waqf institution, religious obligation and access to cash waqf have significant contribution to the endower’s perception to endow cash waqf. Meanwhile, repeated cash waqf behavior will take place if endowers are familiar with waqf institutions and have easy access to cash waqf as these two variables are significantly related to dependent variable. Thus, in order to motivate endowers to repeat cash waqf behavior, continuous promotion to create familiarity together with easy access to cash waqf are vital to encourage repeated charitable behavior.